The Analisis Penerapan Mini Eco-School Project Terhadap Sikap Peduli Lingkungan Siswa Madrasah Ibtidaiyah - Harianto, Rony; Ayuni, Sri; Lailatul Isnaini, Nur; Fausi, Moh. (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study aims to analyze the effectiveness of the Mini Eco-School Project in fostering environmental awareness and responsibility among students of Madrasah Ibtidaiyah Negeri (MIN) 1 Pamekasan. The research is motivated by the growing environmental issues that demand the active role of education in developing ecological awareness from an early age. This study employed a qualitative method with an exploratory case study approach. Data were collected through observation, interviews, and documentation over five weeks of project implementation, which involved activities such as cleanliness habituation, simple waste management, and school greening. The results indicate that before the project, students’ environmental awareness and behaviors were still low and situational. After the project implementation, there was a significant improvement in students’ awareness, responsibility, and intrinsic motivation to maintain school cleanliness. Students began to act proactively, reminding peers who littered, and applying environmental care habits at home. Teachers also observed that the project successfully cultivated ecological character through positive habituation, role modeling, and experiential learning. Thus, the Mini Eco-School Project proved to be an effective strategy for character education based on environmental values, not only enhancing cognitive understanding but also fostering affective and social dimensions of ecological awareness sustainably.